Implementasi Moderasi Beragama Dalam Perspektif Hukum Hindu Melalui Ajaran Tat Twam Asi - Peni, Gelar Sumbogo; Riani, Made (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2025)
Religious moderation is an approach to building a harmonious, tolerant, and peaceful religious life in a pluralistic society. In the context of Indonesia, which has ethnic, cultural, and religious diversity, religious moderation is a strategic solution in preventing conflict and maintaining national unity. This study aims to analyze the implementation of religious moderation in Hindu teachings through the perspective of Tat Twam Asi, a moral teaching that emphasizes universal human values, empathy, and spiritual awareness that all beings are part of the same self. This study uses a qualitative method with a library research approach through analysis of Hindu teaching sources such as the Vedas, Upanishads, Bhagavad Gita, and academic literature related to religious moderation. The results show that the values ​​of religious moderation are inherent in Hindu teachings, particularly in Tat Twam Asi, which teaches the principles of tolerance, compassion, togetherness, mutual respect, and non-violence. The implementation of these teachings is evident in the social life of Hindus, both in interactions between religious communities and in maintaining harmony with others and nature. Thus, the teachings of Tat Twam Asi have strong relevance in strengthening religious moderation and can be used as an ethical foundation in strengthening brotherhood and tolerance in social, national and state life.